2019
DOI: 10.5194/acp-19-10697-2019
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical production of ozone and emissions of NO<sub><i>x</i></sub> and CH<sub>4</sub> in the San Joaquin Valley

Abstract: Abstract. Midday summertime flight data collected in the atmospheric boundary layer (ABL) of California's San Joaquin Valley (SJV) are used to investigate the scalar budgets of NOx, O3, and CH4, in order to quantify the individual processes that control near-surface concentrations, yet are difficult to constrain from surface measurements alone: these include, most importantly, horizontal advection and entrainment mixing from above. The setting is a large mountain–valley system with a small aspect ratio, where … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 68 publications
(108 reference statements)
5
14
0
Order By: Relevance
“…These observations reflect the controls on diurnal ozone variability discussed in similar studies, including nighttime ozone depletion via surface deposition and NO titration, rapid midmorning ozone increases via boundary layer entrainment followed by in situ photochemical production, and diurnal winds facilitating horizontal advection (Jaffe et al, 2018;Trousdell et al, 2019;Oltmans et al, 2019). These effects can be seen to different degrees across the range of site elevations.…”
Section: Ozone Spatiotemporal Patterns In Summer 2018supporting
confidence: 74%
See 2 more Smart Citations
“…These observations reflect the controls on diurnal ozone variability discussed in similar studies, including nighttime ozone depletion via surface deposition and NO titration, rapid midmorning ozone increases via boundary layer entrainment followed by in situ photochemical production, and diurnal winds facilitating horizontal advection (Jaffe et al, 2018;Trousdell et al, 2019;Oltmans et al, 2019). These effects can be seen to different degrees across the range of site elevations.…”
Section: Ozone Spatiotemporal Patterns In Summer 2018supporting
confidence: 74%
“…Higher elevation sites can be above the nighttime inversion and so experience significantly less ozone loss at night (Aneja et al, 2000;Ambrose et al, 2011). Although our study design does not permit us to directly determine the magnitude of depositional loss processes or how it may vary across sites, Trousdell et al (2019) propose that in the San Joaquin Valley, much of the ozone loss at dusk, in the absence of photochemistry and entrainment, is in fact due to surface deposition and not simply titration by rush hour NO emissions. Caputi et al (2019) found overnight losses of approximately 1.2 ppb h -1 in California's San Joaquin Valley.…”
Section: Ozone Spatiotemporal Patterns In Summer 2018mentioning
confidence: 95%
See 1 more Smart Citation
“…Visalia is located about one third of the way from Fresno to Bakersfield, the two most populous cities in the San Joaquin Valley (SJV), and the TOPAZ lidar was colocated with a radar wind profiler and Radio Acoustic Sounding System operated by the San Joaquin Valley Air Pollution Control District (Bao et al, 2008) and a vertically staring Doppler lidar operated by NOAA. Ozone, CO 2 , CH 4 , and other species were also sampled by single-engine Mooney TLS Bravo and Ovation 2 research aircraft operated by the University of California, Davis (UC Davis) and Scientific Aviation (SciAv) (Trousdell et al, 2019) and by the NASA Alpha Jet Atmospheric eXperiment (AJAX) research aircraft (Yates et al, 2015). Details of the sampling techniques and intercomparisons between the lidar and airborne O 3 measurements are described in Leblanc et al (2018) and Langford et al (2019).…”
Section: The California Baseline Ozone Transport Studymentioning
confidence: 99%
“…Widespread agricultural irrigation (Li et al, 2016) and subsidence created by the mountain-valley circulations and persistent North Pacific High (Trousdell et al, 2016) typically cap the afternoon mixed layers below 1 km 10.1029/2019JD031777 (Bianco et al, 2011), and some of the pollution carried into the mountains by the afternoon upslope winds (Panek et al, 2013) is recirculated back over the valley above the shallow boundary layers (De Young et al, 2005;Fast et al, 2012;Gohm et al, 2009;Rampanelli et al, 2004;Zardi & Whiteman, 2013). There, the pollution accumulates in a persistent "buffer layer" (Faloona et al, 2020;Trousdell et al, 2019) that can persist for days or even weeks until dispersed by passing cold frontal systems. During CABOTS, free tropospheric air flowing over the Coast Ranges also carried smoke from the Soberanes Fire into the buffer layer where it mingled with the anthropogenic pollution.…”
Section: Dispersion Of Smoke Into the Sjvmentioning
confidence: 99%